Delivering health interventions to women, children, and adolescents in conflict settings: what have we learned from ten country case studies?. Issue 10273 (6th February 2021) - Singh, Neha S; Ataullahjan, Anushka; Ndiaye, Khadidiatou; Das, Jai K; Wise, Paul H; Altare, Chiara; Ahmed, Zahra; Sami, Samira; Akik, Chaza; Tappis, Hannah; Mirzazada, Shafiq; Garcés-Palacio, Isabel C; et al.
Summary: Armed conflict disproportionately affects the morbidity, mortality, and wellbeing of women, newborns, children, and adolescents. Our study presents insights from a collection of ten country case studies aiming to assess the provision of sexual, reproductive, maternal, newborn, child, and adolescent health and nutrition interventions in ten conflict-affected settings in Afghanistan, Colombia, Democratic Republic of the Congo, Mali, Nigeria, Pakistan, Somalia, South Sudan, Syria, and Yemen. We found that despite large variations in contexts and decision making processes, antenatal care, basic emergency obstetric and newborn care, comprehensive emergency obstetric and newborn care, immunisation, treatment of common childhood illnesses, infant and young child feeding, and malnutrition treatment and screening were prioritised in these ten conflict settings. Many lifesaving women's and children's health (WCH) services, including the majority of reproductive, newborn, and adolescent health services, are not reported as being delivered in the ten conflict settings, and interventions to address stillbirths are absent. International donors remain the primary drivers of influencing the what, where, and how of implementing WCH interventions. Interpretation of WCH outcomes in conflict settings are particularly context-dependent given the myriad of complex factors that constitute conflict and their interactions. Moreover, the comprehensiveness and quality of data remain limited in conflict settings. The dynamic nature of modern conflict and the expanding role of non-state armed groups in large geographic areas pose new challenges to delivering WCH services. However, the humanitarian system is creative and pluralistic and has developed some novel solutions to bring lifesaving WCH services closer to populations using new modes of delivery. These solutions, when rigorously evaluated, can represent concrete response to current implementation challenges to modern armed conflicts.